Impacts of Feeder Reconfiguration on Renewable Resources Allocation in Balanced and Unbalanced Distribution Systems - Zidan, Aboelsood A. (2016)
In this article, network reconfiguration and distributed generation allocation in distribution networks are dealt with simultaneously while imposing an objective of minimizing energy loss. The proposed method, which is based on a genetic algorithm, takes into consideration the uncertainty related to renewable distributed generation output power and the load variability. Three scenarios are assessed to analyze the superiority of the proposed method. In the first scenario, distributed generation units are allocated using the base configuration, followed by network reconfiguration. In the second scenario, distributed generations are allocated after network reconfiguration. In the third scenario, distributed generations are allocated simultaneously with network reconfiguration. The constraints involved include voltage limits, line current limits, and radial topology. Both balanced and unbalanced distribution systems are used as case studies.